Modern production/operations management - Buffa, Elwood S. (Wiley, 1987)
Provides a conceptual and analytical operations management framework for both manufacturing and service firms. The thrust of this new edition is more quantitative in approach and more comprehensive in its discussion of strategic issues. Provides treatments of multi-criteria decision methods, quality control, and operations strategy not found in other texts. Divided into four sections, the first convincingly demonstrates that the operations function is of paramount importance in the success of a firm. The second section presents quantitative models, and the third and final sections discuss the design of operations systems, advanced technologies, strategy, formulation and implementation.